Convergence and prospective of teleducation - Lovatón Sarco, Pedro (2007)
We accept and we are affected by the global impact of Media convergence which obliges our country's adminisrration that is ro say, economic, political, cultural and fam ily institutions ro work in a cybernetic environmenr, informatics and radiotelevision, this creating a "computerized". On the other hand, this phenomenon is not completely done. There's a critical moment and a process which are not enjoyed by sorne sector yet and require an organic attention policy in the education sector. We are referring to distance educati. We have people who maintain their cultura links within their formal acader needs and seek to be competent and interactive. To renew strategies in an une sociery that counts on a lot of resources (arts, language, foods, dwellings, drin projecrs, etc.) and to develop the necessary diagnoses and adapt them to curn demands by redesigning our realities with the help of education and Media.